Threshing crew (Goodhue County Historical Society, 1166 Oak Street, Red Wing, Minnesota 55066; http://www.goodhuehistory.mus.mn.us, 1905)
Boys from Goodhue
United States
Minnesota
Goodhue
Red Wing
Mode of access: Internet.
Keywords: Postcard; Steam engines; Threshing; Farmers; Agriculture